Pharmaceutical preparations in the form of pellets, systematization of information on production methods, study of microstructure and properties of omeprazole pellets - Yerkhova, Anna; Katynska, Maryna (The Ukrainian Scientific Medical Youth Journal, 2021)
The article provides an overview of pharmaceuticals in the form of pellets, systematization of information on production methods, a study of the microstructure and properties of omeprazole pellets. The main purpose of the study is to summarize the cases when the use of such a form as pellets is the most justified, to review drugs in Ukraine containing pellets, to compare pellets from Ukrainian manufacturers (it was decided to take pellets from Arterium Corporation and Farmak) with foreign ones (it was decided to take Teva and ChemoIberica as the foreign manufacturers),to summarize modern methods of pellet production, to study available omeprazole pellets from different manufacturers, compare their properties and justify the method, which was used in production. To compare the properties of pellets from different manufacturers, it was decided to study morphology, density, diameter, the average weight of omeprazole pellets. Investigate and compare the resistance of enteric pellets of omeprazole from different manufacturers to liquid media with different pH values. Based on the received experimental data to explain the possible reason for differences in properties of the investigated pellets. The method included the study of morphology, density, diameter, average weight. Microscopy and gravimetric analysis were used in the work. To study the resistance of enteric pellets to liquid media with different pH values, a method was used that studies the increase in moisture content (after exposure to solutions that mimic the possible pH level of the human stomach) and weight loss after drying or the rate of decomposition of pellets. The object of the study was omeprazole pellets from the manufacturers Arterium Corporation (Kievmedpreparat), Farmak, ChemoIberica (CI), and Teva. The article presents the results of an experiment that showed that all pellets have a tank system, pellets from ChemoIberica, Arterium, and Teva were made by layering for the introduction of the active pharmaceutical ingredient, and pellets from Farmak were made using direct pelleting. Also in the study of intestinal-soluble properties of pellets were calculated indicators of moisture absorption and weight loss after drying. Based on the composition of excipients, which is presented in the instructions to the drugs, it turns out that the role of functional polymer in the production of film coatings in ChemoIberica, Teva, and Farmak this polymer is methacrylate copolymer, and the manufacturer Arterium hypromellose phthalate. Both polymers are used in an oral dosage form as an enteric/enteric coating material for tablets, pellets, or granules. The results of this study may be useful for further improvement of formulas for the production of drugs in the form of pellets.